Candidates' Teaching Practice Experiences in the Natural Disaster Period - Nilay Kayhan; Necla Işıkdoğan Uğurlu (Sakarya University Journal of Education)
Natural disasters cause great damage to society as they cause great destruction and risks. Educational services provided after a disaster have an important role for the children and young people to be able to cope with the trauma experienced. One of the regulations regarding the educational process after a natural disaster is related to the practice courses in higher education institutions. In the scope of regulations made by the Council of Higher Education regarding the teaching practice courses of final-year students in the Faculty of Education, students benefited from the right to complete their practices at higher education institutions in different provinces. This study was carried out at a state university in the Aegean Region. 6 special education teachers determined with purposive sampling participated in the study on a voluntary basis. The data of this study which was conducted in phenomenological design as a qualitative research were collected with the focus group interview technique. The data of the study were analyzed holistically using content analysis. In the findings consisting of four main themes which are Information Resources Sharing and Planning, Professional Expectations and Preparation Process, Educational Life After the Natural Disaster, and About the Path Taken One Step Before the Profession, it was stated that attention was drawn to the up-to-date information of the institutional websites through written and social media explanations of official announcements during the announcement, follow-up, and application processes. The participants emphasized the importance of institutional information and communication in the quality of accommodation, transportation, education, and training practices while making decisions. It could be suggested that teaching practices include holistic preparation based on feedback in the process one step before the profession.